2007
DOI: 10.1021/bi7013135
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Characterization of Pseudomonas aeruginosa Bfd and FPR:  Ferredoxin NADP+ Reductase and Not Ferredoxin Is the Redox Partner of Heme Oxygenase under Iron-Starvation Conditions,

Abstract: Among the 118 genes upregulated by Pseudomonas aeruginosa in response to iron starvation [Ochsner, U. A., Wilderman, P. J., Vasil, A. I., and Vasil, M. L. (2002) Mol. Microbiol. 45, 1277-1287], we focused on the products of the two genes encoding electron transfer proteins, as a means of identifying the redox partners of the heme oxygenase (pa-HO) expressed under low-iron stress conditions. Biochemical and spectroscopic investigations demonstrated that the bfd gene encodes a 73-amino acid protein (pa-Bfd) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 68 publications
6
78
0
Order By: Relevance
“…4). Difficulties in releasing iron from the linear tetrapyrrole in vitro were reported for several HOs (Gisk et al 2012;Reniere et al 2010;Wang et al 2007;Wilks and Schmitt 1998). The efficiency of this final step in heme catalysis often appears to depend on the nature of the redox partner.…”
Section: Discussionmentioning
confidence: 99%
“…4). Difficulties in releasing iron from the linear tetrapyrrole in vitro were reported for several HOs (Gisk et al 2012;Reniere et al 2010;Wang et al 2007;Wilks and Schmitt 1998). The efficiency of this final step in heme catalysis often appears to depend on the nature of the redox partner.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it also remains possible that FprA transfers electrons directly to CysI. It has been shown that P. aeruginosa FprA efficiently transfers electrons from NADPH to heme oxygenase (47). Annotated conserved domains within bacterial and chloroplast CysI proteins include "ferredoxin-like" sequences (48).…”
Section: Discussionmentioning
confidence: 99%
“…Ferredoxin-NADP ? reductase from P. aeruginosa (pa-FPR) was expressed and purified as described before (Wang et al 2007). …”
Section: Production and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…The natural electron donor for PigA from P. aeruginosa PAO1 is pa-FPR (Wang et al 2007). Therefore, we performed additional experiments employing pa-FPR as electron donor instead of the artificial reductant system.…”
Section: Biochemical Characterization Of Pigasmentioning
confidence: 99%